ROS-Dependent Endoplasmic Reticulum Stress Is Involved in Silica-Induced Pulmonary Fibrosis through the GRP78/CHOP/TXNIP/NLRP3 Signaling Pathway in Rats - Han, Gui-zhi; Li, Shuang; Cui, Yuan-yuan; Shao, Bo; Song, Ye; Jiang, Shun-li; Zhang, Zhao-qiang (Chemical research in toxicology, 2025)
Several studies have suggested that silica-induced reactive oxygen species (ROS) stimulate the endoplasmic reticulum to undergo endoplasmic reticulum stress (ERS), which eventually leads to pulmonary fibrosis. However, the mechanisms by which ROS-dependent ERS leads to silicosis and fibrosis remain unclear. In this study, male rats were intratracheally instilled with a single dose of crystalline silica (SiO2) suspension (100 mg/mL, 1 mL) to establish silicosis and then were injected intravenously with 1 mL of N-Acetylcysteine (NAC) (at the dose of 20, 40, or 80 mg/kg, respectively) daily to inhibit ROS-dependent ERS. Rats given a single intratracheal dose of SiO2 suspension and subsequently receiving daily intravenous injections of phosphate buffer solution (PBS) served as models, while those given a single intratracheal dose of PBS and subsequently receiving daily intravenous injections of PBS served as controls. After 40 days, lung samples were taken for pathological observation, and the levels of glucose-regulated protein 78(GRP78), CCAAT-enhancer-binding protein homologous protein (CHOP), thioredoxin-interacting protein (TXNIP), and nucleotide-binding oligomerization domain (NOD)-like receptor family pyrin domain containing 3 inflammasome (NLRP3 inflammasome) were assessed. The results showed that compared with the control group, the lung tissues of the model rats exhibited obvious fibrosis and ERS, accompanied by the elevated levels of GRP78, CHOP, TXNIP, and NLRP3 inflammasome. After ROS were inhibited with NAC, the degree of lung fibrosis and ERS was significantly alleviated, and the levels of the aforementioned cytokines were also reduced. Moreover, the higher the dose of NAC intervention, the more pronounced the effects. The results demonstrated that ROS-dependent ERS is deeply involved in silica-induced pulmonary fibrosis through the GRP78/CHOP/TXNIP/NLRP3 signaling pathway in rats.